Calcitonin gene-related peptide-targeting drugs and Raynaud’s phenomenon: a real-world potential safety signal from the WHO pharmacovigilance database - Gérard, Alexandre O.; Merino, Diane; Van Obberghen, Elise K.; Rocher, Fanny; Destere, Alexandre; Lantéri-Minet, Michel; Drici, Milou-Daniel (Journal of headache and pain, 2022)
Background Migraine is responsible for significant disability and societal burden. Recently, drugs targeting the calcitonin gene-related peptide (CGRP) pathway raised new hopes. CGRP, a potent vasodilator, plays a key role in the pathogenesis of migraine attacks. The deficiency of CGRP is involved in Raynaud’s phenomenon, which consists of abnormal vasoconstriction of the digits. We aimed to assess the potential association of Raynaud’s phenomenon with CGRP-targeting drugs, analyzing real-world data from the World Health Organization (VigiBase®). Methods We queried all reports of Raynaud’s phenomenon involving a CGRP-targeting drug. We sought disproportionate reporting of Raynaud’s phenomenon with these drugs. For this purpose, we relied on the calculation of the Information Component (IC). A positive lower end of the 95% confidence interval (CI) of the IC defines a statistically significant association. As migraine patients are prone to Raynaud’s phenomenon, we also calculated the IC of Raynaud’s phenomenon with CGRP-targeting drugs compared to 5HT1 B/D agonists (triptans), and beta-blockers used in the treatment of migraine. Results Overall, 99 reports of Raynaud’s phenomenon involving CGRP-targeting drugs have been yielded in VigiBase®. The most reported CGRP-targeting drug was erenumab, with 56 reports (56.6%). The median time to onset was 84 days. No fatality was notified, but one patient suffered from gangrene and extremity necrosis. As a whole, CGRP-targeting drugs were significantly associated with Raynaud’s phenomenon, with an IC of 3.3 (95%CI: 3.0–3.5). There was a disproportionate reporting of Raynaud’s phenomenon with CGRP-targeting drugs compared to triptans (IC 0.4; 95%CI: 0.1–0.6) and to beta-blockers (IC 0.5; 95%CI: 0.2–0.7) as well. Conclusions There is a significant disproportionality signal of Raynaud’s phenomenon with CGRP-targeting. This signal stands out when CGRP-targeting drugs are compared to other drugs used in patients with migraine. This study is limited by missing data in pharmacovigilance reports. CGRP-targeting drugs may be subject to Weber effect and reporting bias. Nonetheless, CGRP blockade might be the last straw that disrupts the physiological balance of vascular response in patients at-risk of Raynaud’s phenomenon. Pending further data regarding vascular safety of CGRP-targeting drugs, caution is warranted in these patients.